Work-To-Work Bibliographic Relationships In Medical Subject Areas Based On Functional Requirements For Bibliographic Records (FRBR) During 2006-2010 - Masoud Mohammadi; Seyed Javad Ghazi Mir Saeed; Alireza Noruzi (Tehran University of Medical Sciences, 2013)
Background and Aim: FRBR is one of the models considered in cataloging and work-to-work relationships are introduced as types of bibliographic relationships present in this model. This study examines the distribution of dispersion relationships in medical subject areas based on FRBR model in Persian medical sources published from 2006 to 2010. Materials and Methods: This study is a descriptive survey . Data were obtained from Iranian OPAC ( online public access catalog) . To determine the areas of medical sciences, both LC (Library of Congress) and Dewey Classifications were applied. For data analysis, Excel 2007 was used. Using descriptive statistics, the researcher presented the results in the form of tables and graphs. Results: According to Dewey Classification, 'diseases' was the subject area having the highest number of bibliographic relationships and the lowest frequency belonged to 'experimental medicine'. The analysis based on LC Classification, however, showed that 'internal medicine' had the highest number of bibliographic relationships; Botanic, Thomsonian, Eclectic Medicine, Chiropractic and Alternative medicine subject matters had the lowest bibliographic relationships. Conclusion : Distribution of work-to-work bibliographic relationships in Persian medical sources based on Dewey and LC Classifications is heterogeneous. Despite the obtained apparently heterogeneous results, such a difference cannot be due to differences in the frequency of bibliographic relationships of medical topics because the classification criteria of medical sciences are different in these two systems.